RESOURCE POTENTIAL OF GREEN TRANSFORMATIONS AS A BUSINESS STRATEGY - GARAFONOVA, Olga; YANKOVOI, Roman; KHUDOLEI, Veronika; PІSHСHЕNKО Oleg (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Businesses have a key role to play in the fight against climate change, especially in the critical years up to 2030. Although each company’s situation is unique, business transformation reveals some key factors that can enable the green actions needed in each sector: decision-making guided by a sustainable long-term vision, the ability to translate this into short-term plans and concrete actions, and significant capital investment in sustainable solutions . Successive crises (economic, social, natural and the latest ongoing epidemiological crisis), which systematically affect the economy of many countries around the world, drew attention to the need for urgent and, above all, real implementation of structural changes in the economy. One of these changes is the so-called green transformation, which aims to transform national economies into modern and competitive economic systems with minimal environmental impact, and it covers many different aspects, ranging from obvious changes related to the way available natural resources are used , to the development of environmentally friendly technologies, to transformations in the field of competences and social awareness, including the need for development in the direction of so-called green skills. The article examines the resource potential of green transformations as a business strategy. It is established that the priority of green transformation is to take care of the environment and ensure that more companies start moving to an eco-friendly company. Therefore, when using the resource potential of green transformations, it is necessary to adapt the charters to the environmental company. It is necessary to develop green corporate policies, Plan access to benefits and tax benefits enjoyed by environmental companies, find green funding, and improve internal strategy. At the same time, costs and reputation will improve as part of the transition to an eco-friendly company with green transformations.